Use of Whey and Whey Preparations in the Food Industry – A Review - Królczyk Jolanta B.; Dawidziuk Tomasz; Janiszewska-Turak Emilia; Sołowiej Bartosz (Polish Journal of Food and Nutrition Sciences)
The interest in whey and whey preparations has considerably increased in recent years. Whey and whey preparations are the so-called “forgotten treasure” and, because of their unique properties, they have been “rediscovered” and have been increasingly frequently and successfully used by various production plants in the food industry. They have also been eagerly purchased by consumers who are aware of the role of whey preparations in adequate human nutrition. For many years, there has been a tendency in the food processing industry to use substitutes of ingredients in recipes of many products. This situation can be observed in the case of foods with reduced fat and sugar, or products for lacto-ovo-vegetarians. Whey - and more specifically, its preparations - can also be used as a substitute. According to many literature sources, its use can have a positive impact not only on the consumers’ health but also on the finances of many companies, by reducing the costs of raw materials, and thus production costs. This review paper presents selected uses of whey and whey preparations in the food industry. The uses of whey discussed include: meat and meat products, reduced-fat products, yoghurts and ice creams, cheeses, bakery products, confectionery and pastry products, infant formulas, and whey drinks.